Malawi - Public Expenditures : Issues and Options - World Bank (Washington, DC, 2013)
This report argues that public expenditure outcomes in Malawi, can be improved in the next few years, provided 1) additional spending on priority items is balanced by expenditure cut-backs in low priority areas, so that public expenditures remain within fiscal parameters to restore macroeconomic stability; 2) incentives for improving the budget process are strengthened; 3) intra-sectoral allocations in key sectors, i.e., education, health, agriculture, and roads, focus on key public goods, and, measures to improve spending are enforced; and, 4) areas such as pensions, and parastatals are restructured, so as to reduce future fiscal burden. Balancing additional spending on priority areas within a macroeconomic framework, will require expenditure restructuring, by limiting non-essential spending, to reduce the country's overall deficit, achieve its macro targets, and attain the Heavily Indebted Poor Countries (HIPC) debt relief finance, which should allow additional spending on priority items. Recommendations suggest a shift in expenditures towards social sectors, HIV/AIDS control and prevention, roads management improvement, and, governance to strengthen the budgetary process. And, savings could be generated by reducing ad-hoc expenditures (e.g., maize price interventions), reducing State Officials allocations (e.g., residences, foreign travel, etc.), and, curbing fraud and corruption.